1999
DOI: 10.2494/photopolymer.12.107
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization of Dialkylfumarates with Electron Donor Monomers via Charge-Transfer Complex.

Abstract: Fumarate esters with abstractable hydrogens were found to copolymerize via photoinitiation with a variety of electron donor monomers at a relatively rapid rate under both air and nitrogen. Under air, their copolymerization rates were much faster than monofunctional or difunctional acrylates when a photoinitiator was used to initiate polymerization. Mixtures of dialkylfumarates and N-vinyl formamide (NW) had copolymerization rates faster than dialkylfumarates and N-vinyl pyrrolidone or vinyl ethers. Similar cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Using OP, we first confirmed that the polymerization of the dialkyl maleate esters does not take place on exposure to UV irradiation either alone or together with vinyl ethers in the absence of a photoinitiator. This result agrees with the prior results of Hoyle et al2 and suggests that despite the spectroscopic evidence for the formation of a weak ground state charge‐transfer complex,3 it appears that it is either inactive or inefficient for photoinduced free radical formation. The photoinitiated free radical copolymerizations of dialkyl maleate and fumarate esters with vinyl ethers are significantly inhibited by oxygen.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Using OP, we first confirmed that the polymerization of the dialkyl maleate esters does not take place on exposure to UV irradiation either alone or together with vinyl ethers in the absence of a photoinitiator. This result agrees with the prior results of Hoyle et al2 and suggests that despite the spectroscopic evidence for the formation of a weak ground state charge‐transfer complex,3 it appears that it is either inactive or inefficient for photoinduced free radical formation. The photoinitiated free radical copolymerizations of dialkyl maleate and fumarate esters with vinyl ethers are significantly inhibited by oxygen.…”
Section: Resultssupporting
confidence: 92%
“…However, the inherent toxicity of maleimide monomers makes these systems somewhat problematic for most commercial applications. In a later article,3 the same group examined the photoinitiated alternating copolymerization of N ‐vinyl formamide with dialkyl fumarates. These two monomers form strongly UV absorbing charge‐transfer complexes that are able to initiate polymerization without the use of a photoinitiator.…”
Section: Introductionmentioning
confidence: 99%